Ship Dynamic Positioning Systems Based on Fuzzy Predictive Control - Wang Liyun; Xiao Jianmei; Wang Xihuai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Dynamic Positioning Systems (DPS) is a technique of automatically maintaining the position of vessels within the specified limits by controlling thrusters. This paper introduces a fuzzy predictive control to position vessels. Firstly, the mathematical model of vessel is created and simplified. Then, we use feed-forward compensation to decouple the system. The T-S model is identified by Fuzzy C-Means clustering algorithm and Least Squares method. After that, we use Generalized Predictive Control (GPC) to control the ships in three degrees of freedom (DOF)-surge, sway and yaw. The simulation results show that the fuzzy predictive control can orient the vessels effectively.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3527